Ink and preparation method thereof, luminescent device and preparation method and application thereof
By using ink composed of nanoparticles, silane copolymers and organic solvents, the problem of destruction of alcohol ether organic solvents on the underlying film during the preparation of QLED devices is solved, and more efficient quantum dot luminescent layer film formation and luminescence performance is achieved.
Patent Information
- Application Number
- CN202311114628.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-18
AI Technical Summary
During the preparation of QLED devices, alcohol ether organic solvents easily penetrate into the quantum dot luminescent layer and its underlying film structure, resulting in the destruction of the underlying film.
An ink including nanoparticles, silane copolymers and organic solvents is provided. The ink formed by mixing the silane copolymers, nanoparticles and organic solvents is used to prepare a quantum dot luminescent layer to reduce the penetration of alcohol ether organic solvents.
The quantum dot luminescent layer prepared with this ink can effectively reduce the damage of alcohol ether organic solvents to the underlying film, and improve the preparation quality and luminescence efficiency of QLED devices.
Smart Images

Figure CN119463574A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of quantum dot luminescence technology, and in particular to an ink and a preparation method thereof, a light-emitting device and a preparation method and application thereof. Background Art
[0002] QLED devices using quantum dots as electroluminescent materials have broad application prospects in the fields of solid-state lighting and liquid crystal display. QLED devices usually include a stacked electron transport layer, a quantum dot light-emitting layer, and a hole transport layer. In the preparation process of traditional QLED devices, when preparing an electron transport layer or a hole transport layer on the upper layer of the quantum dot light-emitting layer, alcohol ether organic solvents can easily penetrate into the quantum dot light-emitting layer and the film structure of the lower layer, causing damage to the lower film. Summary of the invention
[0003] Based on this, it is necessary to provide an ink and a preparation method thereof, a film, a light-emitting device and a preparation method and application thereof. The quantum dot light-emitting layer prepared using the ink can reduce the penetration of alcohol ether organic solvents into the film under the quantum dot light-emitting layer during the preparation of the QLED device, thereby reducing the damage of the alcohol ether organic solvents to the film under the quantum dot light-emitting layer.
[0004] In a first aspect, the present application provides an ink, comprising: nanoparticles, a silane copolymer, and an organic solvent;
[0005] The silane copolymer has the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
[0006] In a second aspect, the present application provides a method for preparing an ink, comprising:
[0007] Provide silane copolymers, nanoparticles, and organic solvents;
[0008] mixing the silane copolymer, the nanoparticles and the organic solvent;
[0009] Wherein, the silane copolymer has the following chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
[0010] In a third aspect, the present application provides a light-emitting device, comprising a substrate, a first electrode layer, a light-emitting layer, and a second electrode layer stacked in sequence, wherein the material of the light-emitting layer comprises nanoparticles and a silane copolymer, and the silane copolymer has the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
[0011] In a fourth aspect, the present application provides a light-emitting device, comprising: a substrate, a first electrode layer, a hole functional layer, a light-emitting layer, an electron functional layer, and a second electrode layer arranged in layers;
[0012] The material of the light-emitting layer includes a material having the following chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkoxy group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * represents a connection site, m is a positive integer less than or equal to n, and R 9 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxy group having 1 to 23 carbon atoms and 1 to 3 hydroxy groups.
[0013] In a fifth aspect, the present application provides a method for preparing a light-emitting device, comprising the following steps:
[0014] Providing a substrate, the substrate comprising a substrate and a first electrode layer stacked in layers;
[0015] Transferring any of the above inks or ink prepared by any of the above ink preparation methods onto the first electrode layer and curing the ink to form a light-emitting layer;
[0016] A second electrode layer is formed on the light-emitting layer.
[0017] In a sixth aspect, the present application provides a display panel, comprising any of the light-emitting devices described above or a light-emitting device prepared by any of the light-emitting device preparation methods described above.
[0018] The ink comprises nanoparticles, a silane copolymer and an organic solvent. The silane copolymer can enhance the solubility and film-forming property of the ink, and can adjust the gaps between the nanoparticles, so that the nanoparticles and the silane copolymer are distributed more evenly. Furthermore, the quantum dot light-emitting layer prepared using the ink can reduce the penetration of alcohol ether organic solvents into the film under the quantum dot light-emitting layer during the preparation of the light-emitting device, thereby reducing the damage of the alcohol ether organic solvents to the film under the quantum dot light-emitting layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic diagram of the structure of a QLED device provided in Example 1 of the present application;
[0020] Figure 2 This is a schematic diagram of the QLED device structure provided in Example 2 of the present application. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0023] An embodiment of the present application provides an ink, comprising: nanoparticles, silane copolymers, and an organic solvent;
[0024] Silane copolymers have the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkoxy group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site. It is understood that x and y represent the polymerization degrees of the two monomers in the copolymer, respectively.
[0025] The ink comprises nanoparticles, a silane copolymer and an organic solvent; the silane copolymer can enhance the solubility and film-forming property of the ink, can adjust the gaps between the nanoparticles, and make the nanoparticles and the silane copolymer distributed more evenly. When the ink is used to prepare a light-emitting layer, a light-emitting layer with a solvent barrier function can be formed. When an alcohol ether solvent diffuses into the light-emitting layer, the silane copolymer in the light-emitting layer can undergo an alcoholysis reaction with the alcohol ether solvent, and can reduce the further penetration of the alcohol ether solvent into the lower film of the light-emitting layer.
[0026] In some embodiments, x is 1 to 180 and y is 1 to 230. Alternatively, x is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 68, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 171, 172, 173, 174, 175, 176, 177, 178, 179 or 180. Optionally, y is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 205, 210, 215, 220, 221, 222, 223, 224, 225, 226, 227, 228, 229 or 230.
[0027] In some embodiments, x:y is 0.1 to 1. Alternatively, x:y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.
[0028] In some embodiments, the weight average molecular weight of the silane copolymer is 1000 to 50000. Optionally, the weight average molecular weight of the silane copolymer is 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 12000, 15000, 17000, 20000, 22000, 25000, 27000, 30000, 32000, 35000, 37000, 40000, 42000, 45000, 48000 or 50000.
[0029] In some embodiments, the mass ratio of the silane copolymer to the nanoparticles is 1: 10000 to 1: 10. Within the mass ratio range of the silane copolymer to the nanoparticles, when the ink is used to prepare a quantum dot light-emitting layer, the prepared nanoparticle-silane copolymer composite layer has a good barrier effect on alcohol ether solvents, and the quantum dot light-emitting layer also has a good quantum dot light-emitting efficiency. Optionally, the mass ratio of the silane copolymer to the nanoparticles is 1:10000, 1:9000, 1:8000, 1:7000, 1:6000, 1:5000, 1:4000, 1:3000, 1:2000, 1:1000, 1:900, 1:800, 1:700, 1:600, 1:500, 1:400, 1:300, 1:200, 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20 or 1:10.
[0030] In some embodiments, the silane copolymer includes at least one of a methacryloxysiloxane-styrene copolymer, a methacryloxysiloxane-methacrylate copolymer, a methacryloxysiloxane-styrene derivative copolymer, and a methacryloxysiloxane-methacrylate derivative copolymer.
[0031] In some embodiments, the silane copolymer includes at least one of a methacryloxypropyltrimethoxysilane-methyl methacrylate copolymer, a methacryloxypropyltrimethoxysilane-styrene copolymer, a 3-methacryloxypropyltriethoxysilane-methyl methacrylate copolymer, and a 3-methacryloxypropyldimethylethoxysilane-methyl methacrylate copolymer.
[0032] In some embodiments, the nanoparticles are selected from at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, Cd at least one of CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; at least one of Group IV-VI compounds selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe; - Group V compounds are selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, In NP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InA At least one of lNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dot with a core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dot with a core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, organic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs +ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic perovskite semiconductor is CMX3, wherein C is a carboxamidine group, M is a divalent metal cation, and M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - or I - At least one of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n -2NH3 + or [NH3(CH2) n NH3]2 + , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .
[0033] In some embodiments, the average particle size of the nanoparticles is 1 nm to 20 nm. Within the average particle size range of the nanoparticles, the dispersion effect of the nanoparticles in the solvent is better, and the film-forming effect of the ink for preparing the quantum dot light-emitting layer is better. Optionally, the average particle size of the nanoparticles is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm.
[0034] In some embodiments, the mass ratio of nanoparticles to organic solvent is 1:100 to 1:5. Within the mass ratio range of nanoparticles to organic solvent, the dispersion and film-forming effects of the ink in preparing the quantum dot light-emitting layer are better. Optionally, the mass ratio of nanoparticles to organic solvent is 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, 1:10, 1:9, 1:8, 1:7, 1:6 or 1:5.
[0035] In some embodiments, the organic solvent includes at least one of an aromatic organic solvent and an alkane organic solvent.
[0036] In some embodiments, the organic solvent includes one or more of benzene, toluene, xylene, tetrahydrofuran, dichloromethane, dichloroethane, chloroform, chlorobenzene, nitrobenzene, dioxane, cyclohexane, ethyl acetate, n-butyl acetate, 1-methoxy-2-propyl acetate, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
[0037] In some embodiments, the viscosity of the ink is 0.5 mPa·s to 50 mPa·s. It is understood that the viscosity of the ink refers to the viscosity of the ink at 25° C. Within the viscosity range of the ink, the film-forming effect when the quantum dot light-emitting layer is prepared using the ink is better. Optionally, the viscosity of the ink is 0.5mPa·s, 0.6mPa·s, 0.7mPa·s, 0.8mPa·s, 1mPa·s, 1.2mPa·s, 1.5mPa·s, 1.7mPa·s, 2mPa·s, 2.5mPa·s, 3mPa·s, 3.5mPa·s, 4mPa·s, 4.5mPa·s, 5mPa·s, 6mPa·s, 7mPa·s, 10mPa·s, 12mPa·s, 15mPa·s, 20mPa·s, 25mPa·s, 30mPa·s, 35mPa·s, 40mPa·s, 45mPa·s, 46mPa·s, 47mPa·s, 48mPa·s, 49mPa·s or 50mPa·s.
[0038] In some embodiments, the surface tension of the ink is 20mN / m to 55mN / m. It is understood that the surface tension of the ink refers to the surface tension of the ink at 25°C. Within the surface tension range of the ink, the film-forming effect is better when the ink is used to prepare a quantum dot light-emitting layer. Optionally, the surface tension of the ink is 20mN / m, 22mN / m, 25mN / m, 27mN / m, 30mN / m, 32mN / m, 35mN / m, 37mN / m, 40mN / m, 42mN / m, 45mN / m, 47mN / m, 50mN / m, 52mN / m or 55mN / m.
[0039] Another embodiment of the present application provides a method for preparing ink, comprising:
[0040] Provide silane copolymers, nanoparticles, and organic solvents;
[0041] mixing the silane copolymer, the nanoparticles, and the organic solvent;
[0042] Among them, the silane copolymer has the following chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
[0043] In some embodiments, the silane copolymer is obtained by copolymerizing a first monomer and a second monomer, wherein the first monomer has a structural formula of The structural formula of the second monomer is Among them, R 4 include At least one of the following, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
[0044] In some embodiments, the first monomer includes at least one of 3-(trimethoxysilyl)propyl-2-methyl-2-acrylate, (3-acryloxypropyl)tris(trimethylsiloxy)silane, 3-methacryloxypropylmethyldiethoxysilane, (3-acryloxy)dimethylmethoxysilane, (3-acryloxy)methylbis(trimethylsiloxy)silane, methacryloxymethyltris(trimethylsiloxy)silane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyldimethylethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane and 3-(methacryloxy)propyltrimethoxysilane.
[0045] In some embodiments, the first monomer accounts for 10% to 90% of the silane copolymer by mass percentage. Within the range of the first monomer accounting for the silane copolymer by mass percentage, the polymerization effect is better, and the dispersion effect of the nanoparticles and the silane copolymer is better. Optionally, the first monomer accounts for 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90% of the silane copolymer by mass percentage. Further optionally, the first monomer accounts for 40% to 60% of the silane copolymer by mass percentage.
[0046] In some embodiments, the second monomer includes at least one of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, lauryl methacrylate, diethylhexyl methacrylate, stearyl methacrylate, behenyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, benzyl methacrylate, α-hydroxyethyl methacrylate, β-hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, triethylene glycol monoester, methoxy polyethylene glycol methacrylate, and butoxypropylene glycol methacrylate.
[0047] In some embodiments, the copolymerization of the first monomer and the second monomer is initiated by a free radical initiator, and the free radical initiator includes at least one of an azo initiator, an organic peroxide initiator, an inorganic peroxide initiator, and a redox initiator. The azo initiator includes at least one of azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile, the peroxide initiator includes at least one of a dialkyl peroxide and dibenzoyl peroxide, the inorganic peroxide initiator includes a persulfate initiator, the redox initiator includes an oxidant and a reductant, the oxidant includes at least one of hydrogen peroxide and a hydride oxide, the reductant includes an inorganic reductant and an organic reductant, and the inorganic reductant includes Fe 2+ , Cu + , NaHSO3, Na2SO3 and Na2S2O3, and the organic reducing agent includes at least one of alcohol, ammonium, oxalic acid and glucose.
[0048] In some embodiments, mixing the silane copolymer, the nanoparticles, and the organic solvent comprises the following steps:
[0049] dissolving the silane copolymer in an organic solvent to form an organic solution;
[0050] The nanoparticles are then dispersed in an organic solution.
[0051] Another embodiment of the present application provides a light-emitting device, including a substrate, a first electrode layer, a light-emitting layer, and a second electrode layer stacked in sequence, wherein the material of the light-emitting layer includes nanoparticles and a silane copolymer, and the silane copolymer has the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
[0052] In some embodiments, the thickness of the light-emitting layer is 10 nm to 100 nm. Optionally, the thickness of the light-emitting layer is 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.
[0053] In some embodiments, the materials of the first electrode layer and the second electrode layer are independently selected from one or more of metals, carbon materials and metal oxides, the metals include one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or include a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
[0054] Another embodiment of the present application provides a light-emitting device, comprising a substrate, a first electrode layer, a hole functional layer, a light-emitting layer, an electron functional layer, and a second electrode layer arranged in layers;
[0055] The material of the light emitting layer includes materials having the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkoxy group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * represents a connection site, m is a positive integer less than or equal to n, and R 9At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkoxy group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups. It is understood that the alcohol ether solvent used in preparing the electronic functional layer will penetrate into the light-emitting layer and undergo alcoholysis reaction with the silane copolymer in the light-emitting layer, that is, the solvent molecule R 9 -OH to -OR in silane copolymer 1 The functional groups are partially or fully substituted to prevent further diffusion of the solvent.
[0056] In some embodiments, the material of the light-emitting layer includes a material having the following chemical formula: and materials having the following general chemical formula:
[0057] In some embodiments, the light-emitting device is an upright QLED device, comprising a substrate, a first electrode layer, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer, and a second electrode layer stacked in sequence, wherein the quantum dot light-emitting layer is any of the above-mentioned films or a film prepared by any of the above-mentioned preparation methods.
[0058] In some embodiments, the light-emitting device is an inverted QLED device, comprising a substrate, a first electrode layer, an electron transport layer, a quantum dot light-emitting layer, a hole transport layer, a hole injection layer, and a second electrode layer stacked in sequence, wherein the quantum dot light-emitting layer is any of the above-mentioned films or a film prepared by any of the above-mentioned preparation methods.
[0059] In some embodiments, the material of the hole injection layer is selected from one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, transition metal oxides and transition metal sulfur compounds, the transition metal oxides are selected from one or more of NiO, MoO2, WO3 and CuO, and the metal sulfur compounds are selected from one or more of MoS2, MoSe2, WS3, WSe3 and CuS.
[0060] In some embodiments, the material of the electron transport layer is selected from one or more of doped or undoped inorganic materials and organic materials; wherein the undoped inorganic material is selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP and MgF2; the doped inorganic material includes undoped inorganic materials and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti and Y; the organic material is selected from one or two of polymethyl methacrylate and polyvinyl butyral.
[0061] Another embodiment of the present application provides a method for preparing a light-emitting device, comprising the following steps:
[0062] Providing a substrate, the substrate comprising a substrate and a first electrode layer stacked in layers;
[0063] Transferring any of the above inks or ink prepared by any of the above ink preparation methods onto the first electrode layer and curing the ink to form a light-emitting layer;
[0064] A second electrode layer is formed on the light emitting layer.
[0065] In some embodiments, the curing temperature is 60° C. to 180° C. Optionally, the curing temperature is 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., or 180° C.
[0066] In some embodiments, the curing temperature is achieved by pulsed heating or continuous heating.
[0067] In some embodiments, the curing time is 1 min to 30 min. Optionally, the curing time is 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min.
[0068] In some embodiments, curing is performed under normal pressure or negative pressure.
[0069] In some embodiments, the ink is transferred to the first electrode layer by spin coating, doctor blading, spraying, piezoelectric inkjet printing, or thermal inkjet printing.
[0070] In some embodiments, a method for preparing a light emitting device comprises the following steps:
[0071] Providing a substrate, the substrate comprising a substrate and a first electrode layer stacked in layers;
[0072] sequentially preparing a stacked hole injection layer and a hole transport layer on the first electrode;
[0073] Transferring any of the above inks or the ink prepared by the above ink preparation method onto the hole transport layer and curing it to form a light-emitting layer;
[0074] An electron transport layer and a second electrode layer are stacked in sequence on the light-emitting layer.
[0075] In some embodiments, a method for preparing a light emitting device comprises the following steps:
[0076] Providing a substrate, the substrate comprising a substrate and a first electrode layer stacked in layers;
[0077] preparing an electron transport layer on the first electrode;
[0078] Transferring any of the above inks or the ink prepared by the above ink preparation method onto the electron transport layer and curing it to form a light-emitting layer;
[0079] A hole transport layer, a hole injection layer and a second electrode layer are stacked in sequence on the light emitting layer.
[0080] Another embodiment of the present application provides a display panel, comprising any of the above-mentioned light-emitting devices or a light-emitting device prepared by any of the above-mentioned methods for preparing the light-emitting devices.
[0081] The following are specific embodiments
[0082] Example 1
[0083] Ink preparation
[0084] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0085] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0086] Example 2
[0087] Ink preparation
[0088] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and styrene, has a weight average molecular weight of 5000, and methacryloxypropyltrimethoxysilane accounts for 60% of the silane copolymer by mass.
[0089] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 20% n-decane solvent, 45% n-hexylbenzene, 24% isododecylbenzene, 1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0090] Example 3
[0091] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0092] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.99% methylnaphthalene solvent, 60% n-nonylbenzene, 0.01% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0093] Example 4
[0094] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0095] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.999% methylnaphthalene solvent, 60% n-nonylbenzene, 0.001% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0096] Example 5
[0097] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0098] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized blue CdS / CdZnS quantum dots. Stir for 30 minutes to obtain ink.
[0099] Example 6
[0100] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0101] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized green CdZnSe / CdZnS quantum dots. Stir for 30 minutes to obtain ink.
[0102] Example 7
[0103] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 1000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0104] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0105] Example 8
[0106] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 20,000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0107] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0108] Example 9
[0109] In this embodiment, the silane copolymer is obtained by polymerization of methacryloxypropyltrimethoxysilane and methyl methacrylate, has a weight average molecular weight of 1000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0110] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0111] Example 10
[0112] In this embodiment, the silane copolymer is obtained by polymerizing 3-methacryloxypropyltriethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyltrimethoxysilane accounts for 50% of the silane copolymer by mass.
[0113] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0114] Embodiment 11
[0115] In this embodiment, the silane copolymer is obtained by polymerization of 3-methacryloxypropyl dimethylethoxysilane and methyl methacrylate, has a weight average molecular weight of 2000, and methacryloxypropyl trimethoxysilane accounts for 60% of the silane copolymer by mass.
[0116] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 29.9% methylnaphthalene solvent, 60% n-nonylbenzene, 0.1% silane copolymer and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0117] Example 12
[0118] Preparation of QLED devices
[0119] In this embodiment, the QLED is a positive QLED device. Figure 1The structure is a first electrode layer of indium tin oxide (ITO), a PEDOT:PSS hole injection layer, a 1,2,4,5-tetrakis(trifluoromethyl)benzene (TFB) hole transport layer, a quantum dot light emitting layer, a TiO2 electron transport layer and an Al second electrode layer stacked from bottom to top. The quantum dot light emitting layer is prepared by the ink obtained in Example 1. The preparation method is as follows: the ink is spin-coated on the prepared hole transport layer and the vacuum degree is 1×10 - 5 The mixture was evaporated and dried at 400 torr for 30 min and heated at 100°C for 5 min.
[0120] Example 13
[0121] Preparation of QLED devices
[0122] In this embodiment, the QLED is an inverted QLED device. Figure 2 The structure is an ITO first electrode layer, a ZnO electron transport layer, a quantum dot light-emitting layer, a TFB hole transport layer, a LiF hole injection layer and an Al second electrode layer stacked in sequence from bottom to top. The quantum dot light-emitting layer is prepared by the ink obtained in Example 2. The preparation method is as follows: the ink is spin-coated on the prepared hole transport layer and the vacuum degree is 1×10 -5 The mixture was evaporated and dried at 400 torr for 30 min and heated at 100°C for 5 min.
[0123] Embodiment 14
[0124] Preparation of QLED devices
[0125] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 3.
[0126] Embodiment 15
[0127] Preparation of QLED devices
[0128] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 4.
[0129] Example 16
[0130] Preparation of QLED devices
[0131] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 5.
[0132] Embodiment 17
[0133] Preparation of QLED devices
[0134] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 6.
[0135] Embodiment 18
[0136] Preparation of QLED devices
[0137] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 7.
[0138] Embodiment 19
[0139] Preparation of QLED devices
[0140] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 8.
[0141] Embodiment 20
[0142] Preparation of QLED devices
[0143] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 9.
[0144] Embodiment 21
[0145] Preparation of QLED devices
[0146] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 10.
[0147] Embodiment 22
[0148] Preparation of QLED devices
[0149] The structure and preparation method of the QLED device in this embodiment are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Example 11.
[0150] Comparative Example 1
[0151] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 30% methylnaphthalene solvent, 60% n-nonylbenzene and 10% oleylamine-stabilized red CdSe / ZnS quantum dots. Stir for 30 minutes to obtain ink.
[0152] Comparative Example 2
[0153] Preparation method of ink: add the following components in mass percentage into a single-necked flask in a stirring state: 30% methylnaphthalene solvent, 60% n-nonylbenzene and 10% oleylamine-stabilized blue CdS / CdZnS quantum dots. Stir for 30 minutes to obtain ink.
[0154] Comparative Example 3
[0155] Preparation method of ink: add the following components in mass percentage into a single-necked flask in sequence under stirring: 30% methylnaphthalene solvent, 60% n-nonylbenzene and 10% green CdZnSe / CdZnS quantum dots. Stir for 30 minutes to obtain ink.
[0156] Comparative Example 4
[0157] The structure and preparation method of the QLED device in this comparative example are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Comparative Example 1.
[0158] Comparative Example 5
[0159] The structure and preparation method of the QLED device in this comparative example are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Comparative Example 2.
[0160] Comparative Example 6
[0161] The structure and preparation method of the QLED device in this comparative example are basically the same as those in Example 12, with the only difference being that the quantum dot light-emitting layer is prepared using the ink obtained in Comparative Example 3.
[0162] In the QLED devices prepared in Examples 12 to 22, when the ink prepared in Examples 1 to 11 is used to prepare the quantum dot light-emitting layer, a quantum dot light-emitting layer with a solvent barrier function can be formed. When the alcohol ether solvent diffuses into the quantum dot light-emitting layer, the silane copolymer in the quantum dot light-emitting layer can undergo an alcoholysis reaction with the alcohol ether solvent, which can reduce the further penetration of the solvent into the film under the quantum dot light-emitting layer. The QLED devices prepared in Examples 12 to 22 and the QLEDs prepared in Comparative Examples 4 to 6 were tested for external quantum efficiency. The test results are shown in Table 1 below:
[0163] Table 1
[0164]
[0165]
[0166] It can be seen from Table 1 that in Examples 12 to 22, when the ink prepared in Examples 1 to 11 was used to prepare the quantum dot light-emitting layer, the EQE of the obtained QLED devices was greater than that of the QLED devices prepared in Comparative Examples 4 to 6.
[0167] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0168] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. An ink, characterized in that: include: Nanoparticles, silane copolymers, and organic solvents; The silane copolymer has the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
2. The ink according to claim 1, characterized in that x is 1~180, y is 1~230.
3. The ink according to claim 2, characterized in that x:y is 0.1~1.
4. The ink according to claim 1, characterized in that The weight average molecular weight of the silane copolymer is 1000 to 50000; And / or, the mass ratio of the silane copolymer to the nanoparticles is 1:10000 to 1:
10.
5. The ink according to claim 1, characterized in that The silane copolymer includes at least one of a methacryloxysiloxane-styrene copolymer, a methacryloxysiloxane-methacrylate copolymer, a methacryloxysiloxane-styrene derivative copolymer, and a methacryloxysiloxane-methacrylate derivative copolymer.
6. The ink according to claim 5, characterized in that The silane copolymer includes at least one of a methacryloxypropyltrimethoxysilane-methyl methacrylate copolymer, a methacryloxypropyltrimethoxysilane-styrene copolymer, a 3-methacryloxypropyltriethoxysilane-methyl methacrylate copolymer, and a 3-methacryloxypropyldimethylethoxysilane-methyl methacrylate copolymer.
7. The ink according to claim 1, characterized in that The nanoparticles are selected from at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials; the single structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe , CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, the III-V group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, The compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InN As, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, In At least one of AlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dot with a core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dot with a core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, organic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2 + , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic perovskite semiconductor is CMX3, wherein C is a carboxamidine group, M is a divalent metal cation, and M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2 + 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - or I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n -2NH3 + or [NH3(CH2) n NH3]2 + , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; And / or, the average particle size of the nanoparticles is 1 nm to 20 nm; And / or, the mass ratio of the nanoparticles to the organic solvent is 1:100 to 1:
5.
8. The ink according to claim 1, characterized in that The organic solvent includes at least one of an aromatic organic solvent and an alkane organic solvent.
9. The ink according to any one of claims 1 to 8, characterized in that: The viscosity of the ink is 0.5 mPa·s to 50 mPa·s; And / or, the surface tension of the ink is 20 mN / m to 55 mN / m.
10. A method for preparing ink, characterized in that: include: Provide silane copolymers, nanoparticles, and organic solvents; mixing the silane copolymer, the nanoparticles and the organic solvent; Wherein, the silane copolymer has the following chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
11. The method for preparing ink according to claim 10, characterized in that: The silane copolymer is obtained by copolymerizing a first monomer and a second monomer, wherein the structural formula of the first monomer is The structural formula of the second monomer is Among them, R 4 include At least one of the following, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 5 , R 6 , R 7 are independently selected from hydrogen atoms and alkyl groups having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
12. The method for preparing ink according to claim 10, characterized in that: The first monomer includes at least one of 3-(trimethoxysilyl)propyl-2-methyl-2-acrylate, (3-acryloxypropyl)tris(trimethylsiloxy)silane, 3-methacryloxypropylmethyldiethoxysilane, (3-acryloxy)dimethylmethoxysilane, (3-acryloxy)methylbis(trimethylsiloxy)silane, methacryloxymethyltris(trimethylsiloxy)silane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyldimethylethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane and 3-(methacryloxy)propyltrimethoxysilane.
13. The method for preparing ink according to claim 10, characterized in that: The first monomer accounts for 10% to 90% of the silane copolymer by mass percentage; preferably, The first monomer accounts for 40% to 60% of the silane copolymer by mass.
14. The method for preparing ink according to claim 10, characterized in that: The second monomer includes at least one of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, lauryl methacrylate, diethylhexyl methacrylate, stearyl methacrylate, behenyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, benzyl methacrylate, α-hydroxyethyl methacrylate, β-hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, triethylene glycol monoester, methoxypolyethylene glycol methacrylate and butoxypropylene glycol methacrylate.
15. The method for preparing the ink according to any one of claims 10 to 14, characterized in that: The copolymerization of the first monomer and the second monomer is initiated by a free radical initiator, and the free radical initiator includes at least one of an azo initiator, an organic peroxide initiator, an inorganic peroxide initiator, and a redox initiator.
16. A light emitting device, characterized in that: The invention comprises a substrate, a first electrode layer, a light-emitting layer and a second electrode layer which are stacked in sequence, wherein the material of the light-emitting layer comprises nanoparticles and a silane copolymer, and the silane copolymer has the following general chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxyl group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * indicates a connection site.
17. A light emitting device, characterized in that: include: A substrate, a first electrode layer, a hole functional layer, a light emitting layer, an electron functional layer and a second electrode layer are stacked; The material of the light-emitting layer includes a material having the following chemical formula: Wherein, x and y are positive integers, n is 1, 2 or 3, R is selected from an alkyl group having 1 to 3 carbon atoms, R 1 At least one selected from an alkyl group having 1 to 3 carbon atoms and Si(CH3)3, R 2 is selected from an alkyl group having 1 to 3 carbon atoms, R 3 is selected from an alkylene group having 1 to 3 carbon atoms, R 4 include At least one of the following, where R 5 , R 6 , R 7 Each independently selected from at least one of a hydrogen atom and an alkyl group having 1 to 4 carbon atoms, R 8 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkoxy group having 1 to 23 carbon atoms and 1 to 3 hydroxyl groups; * represents a connection site, m is a positive integer less than or equal to n, and R 9 At least one selected from an alkyl group having 1 to 23 carbon atoms, a cycloalkyl group having 3 to 23 carbon atoms, and an alkhydroxy group having 1 to 23 carbon atoms and 1 to 3 hydroxy groups.
18. The light emitting device according to any one of claims 16 to 17, characterized in that: The thickness of the light-emitting layer is 10 nm to 100 nm.
19. The light emitting device according to any one of claims 16 to 17, characterized in that: The materials of the first electrode layer and the second electrode layer are independently selected from one or more of metals, carbon materials and metal oxides, the metals include one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or include a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
20. A method for preparing a light emitting device, characterized in that: The following steps are involved: Providing a substrate, the substrate comprising a substrate and a first electrode layer stacked in layers; Transferring the ink according to any one of claims 1 to 9 or the ink prepared by the method for preparing the ink according to any one of claims 10 to 15 onto the first electrode layer and curing the ink to form a light-emitting layer; A second electrode layer is formed on the light-emitting layer.
21. The method for preparing a light emitting device according to claim 20, characterized in that: The curing temperature is 60°C to 180°C; And / or, the curing time is 1 min to 30 min.
22. A display panel, characterized in that: A light-emitting device comprising the light-emitting device according to any one of claims 16 to 18, or the light-emitting device according to claim 19, or a light-emitting device prepared by the method for preparing the light-emitting device according to any one of claims 20 to 21.